Physician Burnout: A Lifestyle Medicine Perspective. Issue 2 (March 2021) - Merlo, Gia; Rippe, James
Physician burnout, as described in North America, is a multidimensional work-related syndrome that includes emotional exhaustion, depersonalization, and a low sense of accomplishment from work. More than 50% of physicians were reporting symptoms of burnout prior to the COVID-19 pandemic. This silent epidemic of burnout is bound to become less silent as the pandemic continues. Lifestyle medicine is an evidence-based discipline that describes how daily habits and health practices can affect overall health and well-being of individuals. Lifestyle Medicine can potentially play a significant role in preventing and ameliorating physician burnout. This article explores the burnout process, including the historical context, international definitions, symptoms, and imprecision of the clinical diagnosis. The systemic etiological issues are discussed, and the psychological underpinnings are explored, including physicians' personal vulnerabilities contributing to burnout. The stress response and lifestyle medicine's role in healthy coping are described. A prevention model for risk factor reduction is proposed, focusing on primordial, primary, secondary, and tertiary prevention. Lifestyle medicine clinicians' role in prevention, treatment, and advocacy to ameliorate the potential for burnout is discussed along with specific recommendations.